Musculoskeletal Disorders Mapping among Workers of Community Health Center - Bayu Prastowo; Arys Hasta Baruna; Marinda Yustia Nurfani; Wawat Watini (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: The second most common work-related disease has been identified as musculoskeletal disorders (MSDs). That affect muscles, tendons, ligaments, joints, peripheral nerves, and supporting structures are inflammatory and degenerative conditions. This study identified the job activity of community health centers with the risk of MSDs. Methods: The Nordic musculoskeletal questionnaire (NMQ) was identified as a non-professional way of determining MSDs risk with modifications from statistical investigation models. The study was conducted with fifty-seven respondents of workers at a community health center (CHC). Results: The majority of respondents were female (82%) and showed obesity categories I and II. The correlation between age and work experience is 0.9. A prevalence of MSDs at the hand and wrist of 49% was found. Conclusion: Workers at CHC experienced the mild category of MSDs in the hand and wrist regions. Age and work experience are risk factors for MSDs in CHCs.